Cops on Film: Hollywood's Depiction of Law Enforcement in Popular Films, 1984–2014. Issue 2 (April 2016) - Pautz, Michelle C.
ABSTRACT: With numerous recent incidents in which law-enforcement officers played a role in the deaths of citizens, there is a renewed focus on cops and their actions. Part of that discussion is related to the nation's preconceived notions of cops and where those ideas might originate. Popular culture contributes to those images; this study explores one source of those images: film. More specifically, it investigates the image of law enforcement on the silver screen from 1984 through 2014. With a sample of 34 films and more than 200 cop characters, this study finds a mixed general depiction of law enforcement in movies but a positive depiction of individual cop characters. The prevalent descriptor of those characters was good, hard-working, and competent law-enforcement officers. This exploratory study informs broader discussions about the images of cops found in popular culture.